Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/02692163231165325
|View full text |Cite
|
Sign up to set email alerts
|

The associations between prognostic awareness and health-related quality of life among patients with advanced cancer: A systematic review

Abstract: Background: Prognostic awareness among patients with advanced cancer is important for better palliative and end-of-life care. However, the relationships between prognostic awareness and patient health-related quality of life outcomes remain inconsistent across studies. Critically synthesizing empirical literature will allow for a better understanding of these associations. Aim: To investigate the associations between prognostic awareness and health-related quality of life outcomes among patients with advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This is below the 56.2% (median=66%) of prognostically aware patients from studies conducted in Asia from a recent systematic review by Ng and Ozdemir. 35 In this way, our results were in keeping with the belief of some Filipino physicians 33 and family members 27 that disclosure of a poor prognosis could diminish the patient's hope and will to fight the illness. It also corroborated the traditional practice of family caregivers requesting physicians to conceal the stage of cancer and its prognosis from the patient due to their belief that only God can decide a person's fate.…”
Section: Comparison With Other Studiessupporting
confidence: 83%
“…This is below the 56.2% (median=66%) of prognostically aware patients from studies conducted in Asia from a recent systematic review by Ng and Ozdemir. 35 In this way, our results were in keeping with the belief of some Filipino physicians 33 and family members 27 that disclosure of a poor prognosis could diminish the patient's hope and will to fight the illness. It also corroborated the traditional practice of family caregivers requesting physicians to conceal the stage of cancer and its prognosis from the patient due to their belief that only God can decide a person's fate.…”
Section: Comparison With Other Studiessupporting
confidence: 83%
“…A recent systematic review reported that the association between accurate prognostic awareness and quality of life remains controversial ( 25 ). Amongst the 25 included instances (20 studies) of investigating the association between accurate prognostic awareness and depressive symptoms, two reported improvement, nine worsened and 14 found no significant association.…”
Section: Prognostic Awarenessmentioning
confidence: 99%
“…Previous studies have reported that patients who are very close to death are also more likely to acknowledge that they are terminally ill, which reflects accurate prognostic awareness ( 36–38 ). Prognostic awareness may also be influenced by culture; for example, prognostic awareness tends to be better in Asian countries than in Western ones ( 25 ). The tendency to have an accurate understanding of one’s prognosis in Asia contradicts that non-disclosure of prognosis remains prevalent in the region ( 39 ).…”
Section: Prognostic Awarenessmentioning
confidence: 99%